Computer game as a pragmatic concept: ideas, meanings, and culture. (April 2020) - Karhulahti, Veli-Matti
This article discusses the 'computer game' as a pragmatic concept. A dual nature of the computer game as both a pragmatic idea and a pragmatic meaning is introduced. Practical meanings of the computer game correspond with the concrete effects that engaging with computer games produces in an individual. Practical ideas of the computer game correspond with the subjectively constituted conceptual families concerning the computer game's assumed practical meaning. Individual computer games can be considered flat or round depending on the range of their practical meanings. Thus, the article contributes to the study of cultural objects by offering a framework for examining the evolution and existence of such objects as cross-cultural practical entities – less in terms of communication, media, and materiality, and more in terms of concrete actions and events that individuals across societies commence and conceptualize.